1990
DOI: 10.1097/00132586-199012000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anaesthesia on the QT Interval

Abstract: The QT interval, which is measured from the start of the Q wave (or the R wave when no Q wave is present) to the completion of the T wave, reflects the duration of electrical ventricular systole. The duration of systole varies with heart rate and therefore the measured QT interval is often corrected for heart rate using the following formula, in which QTc represents the rate corrected value: QTc = Qt/VRR interval The QTc interval is normally less than 440 ms [1]. Increased serum concentrations of noradrenaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 3 publications
(3 reference statements)
1
14
1
Order By: Relevance
“…Propofol-induced prolongation of the QTc interval has been observed in various studies (17)(18)(19). In the present study, the QT interval was prolonged after propofol injection, but we did not observe any QTc prolongation with propofol usage.…”
Section: Discussioncontrasting
confidence: 69%
“…Propofol-induced prolongation of the QTc interval has been observed in various studies (17)(18)(19). In the present study, the QT interval was prolonged after propofol injection, but we did not observe any QTc prolongation with propofol usage.…”
Section: Discussioncontrasting
confidence: 69%
“…Propofol prolonged the QTc interval significantly in some studies [26,27], while others showed it to have little or no effect [4,7]. Although the duration of propofol infusion was short compared to some other studies [4,7], over the time studied it did not prolong the QTc intervals before laryngoscopy.…”
Section: Discussionmentioning
confidence: 87%
“…[40][41][42][43] In our study, the patients with aLQTS often had the syndrome at the time of ICU admission (30%), or aLQTS developed soon after their admission to the unit (70%); the mean time of onset was 10.6 hours after ICU admission. Our sample included 8 patients who had major surgery and returned to the ICU from the operating room.…”
Section: Medications and Alqtsmentioning
confidence: 93%
“…(Critical Care Nurse. 2012;32 [5]: [32][33][34][35][36][37][38][39][40][41] Feature ©2012 American Association of Critical-Care Nurses doi: http://dx.doi.org/10.4037/ccn2012900…”
Section: Acquired Long Qt Syndrome: Frequency Onset and Risk Factormentioning
confidence: 99%
See 1 more Smart Citation